Nursing consultation in the Family Health Strategy: Prevention of overweight and childhood obesity (Research, Society and Development, 2020)
The present study aims to describe the nursing consultation, as well as the shared consultation of the nurse working in the Family Health Strategy, for the prevention of the underweight and childhood obesity. This is a qualitative, descriptive and exploratory study, whose scenario was composed of five Family Health Clinics located in Programmatic Area 3.1 in the city of Rio de Janeiro, Brazil. The study sample consisted of 12 nurses, where data were collected through semi-structured interviews and analyzed through Content Analysis. From the process of analyzing the statements of the interviewees, two thematic categories emerged: 1) Nursing consultation for the detection overweight and childhood obesity and 2) Shared consultation to monitor overweight and obese children. Nurses' identifications were identified for the prevention of overweight and childhood obesity during the nursing consultation, as well as the consultation shared with other professionals of the Family Health Strategy team. It is noteworthy that the early detection of overweight and obesity in children contributes to the prevention of chronic non-communicable diseases.